Mortality and incidence of cancer of workers in the man made vitreous fibres producing industry: an international investigation at 13 European plants. Issue 4 (November 1984) - Saracci, R; Simonato, L; Acheson, E D; Andersen, A; Bertazzi, P A; Claude, J; Charnay, N; Esteve, J; Frentzel-Beyme, R R; Gardner, M J
Abstract : A total of 25 146 workers at 13 plants producing man made mineral fibres (MMMF) in seven European countries (Denmark, Finland, Federal Republic of Germany, Italy, Norway, Sweden, and United Kingdom) were studied in a historical cohort investigation. At 12 of the 13 plants an environmental survey was carried out to determine present day concentrations of airborne man made mineral fibres that showed levels of respirable fibres usually below 1 f/ml and most commonly in the range 0.01 to 0.1 f/ml. Workers were entered into the cohort at the moment of their first employment at one of the 13 factories (which started to operate between 1900 and 1955), and were followed up to at least 31 December 1977. Three per cent of the workers were lost to follow up. National death rates and national cancer incidence rates, where applicable, were used for each of the seven countries for comparison with the workers' cohort. A single death from mesothelioma was reported out of a total of 309 353 person-years of observation. No consistent differences (within and between plants) were noted between observed and expected numbers concerning individual causes of death or individual cancer sites, apart from lung cancer. For this cause a tendency was observed for the standardised mortality ratio (SMR) to increase with time from first employment. When the data from all the plants were pooled a statistically significant raised SMR of 192 (17 observed, 8.9 expected; 95% confidence interval 117-307) appeared in the group with 30 years or more since first employment. The relevance of this finding, to which different factors including uncontrolled confounders such as smoking habits may have contributed, cannot be established at present. The result is suggestive, however, of an increased risk associated with the man made mineral fibres working environment of 30 or more years ago.